Comparative evaluation of linear dimensional changes of four commercially available heat cure acrylic resins - Saryu Arora; S K Khindaria; Sushant Garg; Sanjay Mittal (Wolters Kluwer Medknow Publications, 2011)
Context: Heat cured acrylic resins undergo dimensional changes during polymerization. Dimensional changes which occur in the heat cure acrylic resins are shrinkage and expansion which affects the fit of the denture and occlusal relationship. Aims: The purpose of this study was to access the linear dimensional changes of four heat cure acrylic resins before and after curing and compare the changes among four different acrylic brands. Materials and Methods: Twenty four patients irrespective of age and sex were taken and four commercially available brands were procured. After the teeth arrangement on the mandibular trial denture, two pins were fixed in central fossae of first molar on both sides and one pin in the cingulum of left central incisor. Meliodent heat cure acrylic resin was used in Group A; Trevalon heat cure acrylic resin was used in Group B; Triplex heat cure acrylic resin was used in Group C and Vertex heat cure acrylic resin was used in Group D. Linear measurements of the trial wax up before and after curing and before and after finishing and polishing were measured and compared. Collected data was analyzed with analysis of variance and 't' test at 95% level of confidence (P=0.05). Results: The maximum percentage changes were seen in cases of Group A (Meliodent) followed by Group B, Group C and Group D (Trevalon, Triplex and Vertex). Meliodent showed the highest percentage change i.e. 1.18% and Vertex showed least percentage change of 0.37 %. Conclusions: Shrinkage occurred after curing and after finishing and polishing, which varies significantly with the four commercially available heat cure acrylic resins. Among the four different brands of heat cure acrylic resin Group D (Vertex) had the least linear dimensional changes after curing and after finishing and polishing, so that D (Vertex) could be the material of choice for fabrication of complete denture among the four brands.